Coping Using Sex, Health-Related Behaviors, and Mental Health During COVID-19 Lockdown in the UK - Daly, Natasha; Jones, Andrew; Garofalo, Carlo; Uzieblo, Kasia; Robinson, Eric; Gillespie, Steven M. (Frontiers in Psychiatry, 2022)
Background: Peoples’ sexual behaviors have changed during the period of enforced COVID-19 social distancing, in some cases, to cope with negative feelings during lockdown. Research on coping using sex is relatively restricted to samples of men with a history of sexual offending, and it is unknown whether coping using sex is associated with health-related behaviors and mental health in the general population. Aim: We examined if coping using sex before and during lockdown was associated with adverse outcomes (i.e., self-perceived reduction in health-related behaviors and mental health) in a community sample. Hypotheses: We hypothesised that participants who reported greater use of sex to cope in the weeks preceding lockdown would show a greater decline in health-related behaviors and mental health during lockdown. Furthermore, that changes in coping using sex resulting from lockdown would account for further variance in the worsening of health-related behaviors and mental health. Methods: Participants were UK residents, aged 18-60 years, and fluent in English. 789 participants completed an online survey, providing demographic information, self-reported social distancing, loneliness, and coping using sex over a 14-day period during lockdown, and retrospectively preceding lockdown. Outcomes: Participants reported perceived changes in health-related behaviours and mental health symptomatology during lockdown compared to before the pandemic. They also self-reported levels of stress, anxiety and depression during lockdown. Results: Greater coping using sex prior to lockdown predicted positive change in health-related behaviors, for example, higher scores were associated with participants reporting having exercised and slept more. It was also associated with higher trait levels of anxiety, stress and depression during lockdown. Changes in coping using sex from before to during lockdown did not predict perceived changes in health related behaviors or mental health symptomatology. Conclusions: Overall, greater coping using sex prior to lockdown was associated with worse mental health symptomatology during lockdown (anxiety, depression and stress), however, it was also associated with perceived positive change in health-related behaviours compared with before lockdown. This suggests that coping using sex may be associated with negative emotional reactions during lockdown, but may also be linked with positive change in health-promoting behaviors.